2022
DOI: 10.14704/web/v19i1/web19129
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Awareness in University Students According to Gender and Age

Abstract: Environmental awareness is the constant articulation that exists between man and his environment. For this, the human being relies on his experiences, wisdom and praxis. The objective was to describe the levels of environmental awareness of students of the health career. The approach was quantitative, of a substantive type and a non-experimental, transactional design. For this study, the sample consisted of 500 students drawn through probability sampling. The technique used was the survey and the instruments w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…According to the results of the participants' age groups, in the overall scale and in all sub-dimensions, the participants between the ages of 19-21 reported higher scores on the level of perception of the social responsibilities of the university, where the research was conducted, compared to the participants aged 25+, unlike the findings of Garay (2021).…”
Section: Findings Discussion and Resultsmentioning
confidence: 67%
See 2 more Smart Citations
“…According to the results of the participants' age groups, in the overall scale and in all sub-dimensions, the participants between the ages of 19-21 reported higher scores on the level of perception of the social responsibilities of the university, where the research was conducted, compared to the participants aged 25+, unlike the findings of Garay (2021).…”
Section: Findings Discussion and Resultsmentioning
confidence: 67%
“…On the other hand, a difference was found in favor of female students in the "Transferring Social Responsibility Consciousness to Students" sub-dimension. Although there was a difference in the gender variable only in this sub-dimension not in the scale total results, the difference in favor of females is a very common situation in the relevant literature (Batur, 2015;Garay, 2021;González-Rodríguez et al, 2014;Kiezel, 2021;Kocabaş, 2014;Yeğintürk, 2019;Yetiş, 2019;Yıldırım, 2019;Wang & Juslin, 2012).…”
Section: Findings Discussion and Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…The students at UAEU are achieving higher scores when compared to a study that examined the levels of environmental knowledge among 500 students pursuing a career in health. Their study revealed that 45.8% of all students displayed inadequate levels of environmental awareness, [23]. The UAEU population score is also better than among university students in northwestern Mexico [24] and 50 students of classes VIIA and VII C [25], and students at the Budapest Metropolitan University were score almost the same regarding the concept of environmental knowledge [26].…”
Section: Comparative Knowledge Attitudes and Practices In University ...mentioning
confidence: 97%
“…The progress and challenges is the construction of a socially responsible higher education system in Latin America [28,29]. Market -and government-based higher education reforms in Latin America [8]; UNESCO's supranational influence on Latin American higher education [40]; the unconsummated bioethical paradigm of social responsibility [33] ethical values and their implication ethical values and their implication with university social responsibility [13,14] ethical values and their implication with university social responsibility university social responsibility and organizational factors for its implementation [41]; volunteering in the framework of university social responsibility [48] university social responsibility in the framework of university social responsibility cross-cultural social representations about the concept of university social responsibility [3] social responsibility in university students according to gender and age [37]; main factors influencing the dissemination of information on corporate social responsibility on university websites [45] problem-based learning and didactic strategies of capstone courses for university social responsibility [24] among other studies that reveal that the production on university social responsibility is a relatively young field that allows the projection of future studies [17].…”
Section: Introductionmentioning
confidence: 99%